MODELING AXL RECEPTOR TYROSINE KINASE EXPRESSION AND FUNCTION IN BLADDER CANCER CELLS: ITS IMPACT ON CELL MOTILITY - Milov, Vitaliy (Nazarbayev University School of Sciences and Humanities, 2025)
Bladder cancer was the ninth most incident cancer type in 2022. Receptor tyrosine kinases, such as TAM receptors, are promising targets for anti-cancer therapies. By acting upstream of MAPK and EMT pathways, a TAM family member AXL was linked to poor survival, chemotherapy resistance, and metastasis in gastric and breast cancers. This thesis investigated the role of AXL in cell motility in bladder cancer cell lines, as the exact mechanisms and cell velocities had not been reported before. Since ZEB1 is a transcriptional activator of AXL and EMT, we also investigated the effect of ZEB1 knockout on AXL expression and cell motility. Data demonstrated that RT112-derived cell lines expressing AXL mutants exhibited faster cell front velocity than the parental AXL-negative RT112 cells, even in the absence of an AXL ligand. We also reported that ZEB1 knockout in T24 cells downregulated AXL but did not affect cell motility. These results indicated that AXL may act in a ligand-independent manner in bladder cancer cells. Therefore, targeting its kinase activity may not be an efficient therapeutic approach in bladder cancer.
Keywords: Bladder cancer; AXL receptor; ZEB1 knockout; Biomarker; Wound healing; type of access: embargo